Maintaining migration during a pandemic - Cairns, D.; Clemente, M. (The immobility turn: Mobility, migration and the covid-19 pandemic, 2023)
Having looked at the impact of the pandemic on the tourism industry and the mobility of international students, in this chapter we turn our attention towards labour migration. This change of emphasis may appear strange to some readers, with migration traditionally seen as separate from what are considered ‘softer’ forms of mobility. However, while the experience of moving to another country for employment purposes substantially differs from other forms of global circulation, all three of these mobilities depend on the existence of a fully functioning international travel infrastructure and relatively open national borders. We can, therefore, anticipate a certain amount of shared experience among people on the move, even if their experiences are fundamentally different in many other respects.